Platelet Count/Spleen Thickness Ratio and the Risk of Variceal Bleeding in Cirrhosis With Esophagogastric Varices - Liu, Huimin; Zhang, Qun; Gao, Fangyuan; Yu, Hao; Jiang, Yuyong; Wang, Xianbo (Frontiers in Medicine, 2022)
Introduction The platelet count/spleen thickness ratio (PC/ST ratio) is associated with the grade of esophagogastric varices (EGV) in cirrhotic patients, but little is known about its relationship with esophagogastric variceal bleeding (EGVB). The aim of this study was to investigate the association between the PC/ST ratio and the risk of EGVB within 1 year in cirrhotic patients. Methods A total of 1,354 patients with cirrhosis who had EGV were enrolled in this cohort study. A logistic regression model was used to determine the association between the PC/ST ratio and the risk of EGVB within 1 year in patients with cirrhosis by adjusting the PC/ST ratio with all the important clinical variables and confounders. Results The quartile values of the PC/ST ratio were 1.01, 1.36, and 1.98, respectively. The PC/ST ratio was an independent risk factor for variceal bleeding in cirrhotic patients with moderate or severe EGV. After adjusting for multiple variables, the relationship was still unchanged. The odds ratios of the first EGVB in these patients were 5.07-fold at non-adjustment and 3.28-fold after multivariate adjustment. The odds ratios of rebleeding in these patients from the lowest to the highest quartile were 2.34-fold at non-adjustment and 2.01-fold after multivariable adjustment. The PC/ST ratio ≤ 1.36 elevated the 1-year risk of first-time variceal bleeding or rebleeding in cirrhotic patients with moderate or severe EGV (All P < 0.05). Conclusion The PC/ST ratio ≤ 1.36 is an independent risk factor for the onset of first bleeding or rebleeding in cirrhotic patients with moderate or severe EGV.